Differentially Fed, Dual-Band Dual-Polarized Filtering Antenna With High Selectivity for 5G Sub-6 GHz Base Station Applications - Li, Yapeng; Zhao, Zhipeng; Tang, Zhaoyang; Yin, Yingzeng (IEEE transactions on antennas and propagation, 2020)
In this communication, a novel dual-band dual-polarized filtering antenna with high selectivity is proposed. By etching four slots at each side of a square radiating patch, dual operation bands as well as a natural radiation null between the two bands are observed. Another two radiation nulls are generated by introducing a novel feeding structure, which is composed of a microstrip line with open-circuit stepped-impedance resonators (OCSIRs). Thus, a dual-band bandpass filtering response of the realized gain is obtained. Each polarization of the antenna is differentially fed, and the differential port isolation is better than 37 dB. A prototype of the antenna element and a 1× 4 array is fabricated and tested to validate our design. Measured results show that the antenna element has dual operation bands of 3.28-3.71 and 4.8-5.18 GHz for VSWR < 1.5. Besides, a high out-of-band gain-suppression level which reaches 17.7 dB is also obtained. Good performance of the proposed antenna makes it a promising candidate for 5G sub-6 GHz base station systems.